Utopian generations : the political horizon of twentieth-century literature - Brown, Nicholas, 1971- (Translation/transnation., 2005)
Utopian Generations develops an interpretive matrix for understanding world literature--one that renders modernism and postcolonial African literature comprehensible in a single framework. African literature has commonly been seen as representationally naïve vis-à-vis modernism, and canonical modernism as reactionary vis-à-vis postcolonial literature. What brings these two bodies of work together, argues Nicholas Brown, is their disposition toward Utopia or "the horizon of a radical reconfiguration of social relations."--Publisher's description.